Synthesis of nanocrystalline zirconia-based powder for surgery implants and study of radionuclides content in it - Shevchenko, A.V.; Lashneva, V.V.; Dubok, V.A.; Dudnik, E.V.; Tsukrenko, V.V.; Ruban, A.K.; Trishin, V.V.; Malyuk, I.A. (Functional Materials, 2014)
Nanocrystalline powder of ZrO₂ (5 % Y₂O₃, 3 % CeO₂) has been synthesized. The powder is developed for manufacture of ceramic implants for bone surgery. Physico-chemical properties of the powder and its radioactivity have been examined. It is shown that the proposed technology allows to produce the nanocrystalline ZrO₂ based powder of high chemical purity and high activity for sintering. Ceramics made of the powder provides the high reliability and assures long term service in the aggressive environment of a living organism. The specific radioactivity of the powder is (1.3 ± 0.4) Bq/kg and is caused by the presence in the powder of natural radionuclide ²²⁶Ra. Radioactivity of the synthesized powder is more than 100 times below the norm accepted by the international standards for ceramic materials based on T-ZrO₂ for surgical implants.